Campur Kode dalam Film Eumpang Breuh Karya Imran Nyak Abeudo - Salsabilla Julnadi; Ramli Ramli; Armia Armia (JIM Pendididikan Bahasa dan Sastra Indonesia, 2019)
The study was titled “Mixed Code in The Film Eumpang Breuh By Imran Nyak Abeudo”. The formulation of this research problem is how the mixed form of code contatained in the film Eumpang Breuh. The purpose of this study describes the mixed forms of code in the film Eumpang Breuh. The benefits of this research can theoretically be used as a science and insight for any party who wants to develop linguistics, especially the sociolinguistic field with regard to mixing codes. Practically this research is useful for the author as well as the reader, the benefits for the author with the existence of this research will deepen the science and understanding of the mix of codes. The benefits for readers can be additional information fot both the public and subsequent researchers about the knowledge of mixed codes. The mothod usedsin thishstudy ishqualitative descripticehmethod. Theudata collection techniqueshused inuthis studyhare listening andirecordingotechniques. Theoresearch data is derived from the words spoken by the characters in the film Eumpang Breuh. Theoresults ofothis studyphave six formspof mixedpcode. First, thepinsertion ofyelements in the form of words with classes of nouns, verbs, and adjectives. Second, thepinsertion ofyelements inkthe formuof pharasespwith verba phrase types, nominal phrases, presupositional phrases, and adjective phrases. Third, the insertion of baster-tangible elements. Fourth, theoinsertion ofuelements inhthe formlof duplication. Fifth, theoinsertion oflelements ingthe formaof idioms. Sixth, theainsertion ofnelements injthe formuof clauses. Based onothehresults of the analysis, obtained 57 mixedncodes, including 34 mixedpcode inithe formhoflwords, 9 mixed inothe formbof phrases, 8 mixedgcode inkthe formfof baster, 3 mixedicode inhthe formbof duplication, 1 mixedkcode infthe formdof expressionsgor idioms, ando2 mixedhcodes infthe formhof clauses.